Thermodynamic Study of Hydrolysis Reactions in Aqueous Solution from Ab Initio Potential and Molecular Dynamics Simulations - S. Tolosa; A. Hidalgo; J. A. Sansón (Journal of Chemistry)
A procedure for the theoretical study of chemical reactions in solution by means of molecular dynamics simulations of aqueous solution at infinite dilution is described using ab initio solute-solvent potentials and TIP3P water model to describe the interactions. The procedure is applied to the study of neutral hydrolysis of various molecules (HCONH2, HNCO, HCNHNH2, and HCOOCH3) via concerted and water-assisted mechanisms. We used the solvent as a reaction coordinate and the free energy curves for the calculation of the properties related with the reaction mechanism, namely, reaction and activation energies.